Here's the question you clicked on:
krissywatts
ues substition method to fin solution sets: I need step by step help 2a+4b=-24 a=20-2b
In the substitution method, you first need to solve one equation for one variable. In this case, that step is already done because the second equation shows what a is equal to. In other words, the second equation is already soved for a.
The second step is to substitute the variable a in the first equation with what a is equal to in the second equation. Since a = 20 - 2b, everywhere you see a in the firtst equation, wrtite 20 - 2b
i have a+b=-12 a+2b=20 is this correct?
No. The first equation is 2a + 4b = -24 Where you see a, write (20 - 2b) You should have no a's left there.
i get -4 is this correct?
as my finale answer
You ask for step by step help. I give you step by step help, but you skip a bunch of steps. You still haven't shown what you got after the substitution.
The first equation is 2a + 4b = -24 Where you see a, write (20 - 2b)
Where is it then? It should look like this: 2a + 4b = -24 2(20 - 2b) + 4b = -24